Dietary Supplementation With High Fiber Alleviates Oxidative Stress and Inflammatory Responses Caused by Severe Sepsis in Mice Without Altering Microbiome Diversity - Zhang, Yuanyuan; Dong, Aili; Xie, Keliang; Yu, Yonghao (Frontiers in Physiology, 2019)
In this study, we demonstrated the effects of a high-fibre diet on intestinal lesions, oxidative stress and systemic inflammation in a murine model of endotoxemia. C57BL/6 mice were randomly assigned to 4 groups: the control group (CONTROL), which received a commercial normal-fibre rodent diet comprising normal fibre; a CLP group, which received a commercial normal-fibre rodent diet and underwent caecal ligation puncture (CLP); a high-fibre group (HFG), which received a commercial high-fibre rodent diet; and a high fibre + CLP group (HFCLP) which received a commercial high-fibre rodent diet and underwent CLP (30%). The sepsis model was created via CLP after 2 weeks of dietary intervention. Notably, dietary high-fibre supplementation in HFCLP group improved survival rates and reduced bacterial loads, compared with CLP alone. In the HFCLP group, dietary fibre supplementation decreased the serum concentrations of pro-inflammatory cytokines such as tumour necrosis factor-α (TNF-α), interleukin 6 (IL-6) and high-mobility group protein 1 (HMG-1) but raised the concentration of interleukin 10 (IL-10), compared with the levels in CLP mice. Meanwhile, high-fibre supplementation increased the relative proportions of Akkermansia and Lachnospiraceae. These data show that dietary high-fibre supplementation may be therapeutic for sepsis-induced lesions.